Comparison of Fund Management Systems in Conventional Insurance and Sharia Insurance - Aicha Azdina Adly Fesya; Salsabilla Hamdi; Larasati Ritonga; Zaldy Ichsan Febrian; Ilham Soleh Tanjung (ISNU Sumatera Utara, 2026)
Insurance is a crucial instrument in the financial system, serving as a means of risk management. In Indonesia, insurance practices have developed into two main systems: conventional insurance and sharia insurance, which differ fundamentally, particularly in fund management. This article aims to compare fund management systems in conventional and sharia insurance, based on a review of previous research, laws and regulations, and relevant literature. The research method used is library research with a qualitative descriptive approach. The results indicate that fund management in conventional insurance is based on the principle of risk transfer, with a system of pooling premiums owned by the company, and investment management that potentially contains elements of riba, gharar, and maisir. Meanwhile, sharia insurance applies the principle of risk sharing through tabarru' and tijarah contracts, with the separation of participant funds from company funds, and investment management that must comply with sharia principles. Furthermore, differences in fund management are also reflected in the underwriting surplus mechanism and oversight by the Sharia Supervisory Board. Thus, it can be concluded that the fund management system in Islamic insurance has more transparent characteristics and is oriented towards the principles of justice and mutual assistance, in contrast to conventional insurance which is oriented towards company profits.